ANTANAS MACEINA’S NATIONAL EDUCATION IDEAS IN THE CONTEXT OF GLOBALISATION - Aramavičiūtė, Vanda (Acta Paedagogica Vilnensia, 2008)
The article makes an attempt to highlight and actualise the key ideas of A. Maceina on national education and their value in our modern society under conditions of globalisation. These ideas, inspiring the wish and attempts to cognise and nurture own NATIONAL vocation, to involve the nation into the international life and simultaneously focusing on nation’s protection from loosing own identity, are of utmost importance in many aspects nowadays. On the other hand, national education ideas get a response among apologists, who perceive national identity as existence and survival of an individual within the same ethnic group, which is considered to be their nation on the basis of shared geographic, linguistic and cultural features. Following the systemic principle which sees NATIONAL education as an integral phenomenon, the focus is laid on A. Maceina’s conception of the key notions in national education: nation and native land. An attempt is made to reveal functions, goals and objectives of A. Maceina’s national education, to highlight external and internal factors conditioning efficient national education and to describe NATIONAL education aids. The author expresses the idea that penetration into the depth of elements of A. Maceina’s national education would also ensure a more purposeful development of fundamental education theory and methodology.